2023
DOI: 10.3390/healthcare11152207
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Exercise, Cognitive Behavioral Therapy, and Pharmacotherapy on Improving Sleep in Adults with Chronic Insomnia: A Systematic Review and Network Meta-Analysis of Randomized Controlled Trials

Abstract: Despite the well-established treatment effectiveness of exercise, cognitive behavioral therapy for insomnia (CBT-I), and pharmacotherapy on improving sleep, there have been no studies to compare their long-term effectiveness, which is of clinical importance for sustainable management of chronic insomnia. This study compared the long-term effectiveness of these three interventions on improving sleep in adults with chronic insomnia. MEDLINE, PsycINFO, Embase, and SPORTDiscus were searched for eligible reports. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Simple and brief exercise training demonstrated high acceptability and exercise adherence, proving effective in alleviating the severity of sleep disorders. Yu et al ( 88 )compared the long-term effects of exercise therapy, CBT-I, and pharmacotherapy on improving sleep in adult patients with chronic insomnia. Their findings suggested that both exercise and CBT-I manifested better long-term effects in improving sleep, while pharmacological interventions were less effective in the long run.…”
Section: Comparison Of Exercise Therapy With Other Treatment Methodsmentioning
confidence: 99%
“…Simple and brief exercise training demonstrated high acceptability and exercise adherence, proving effective in alleviating the severity of sleep disorders. Yu et al ( 88 )compared the long-term effects of exercise therapy, CBT-I, and pharmacotherapy on improving sleep in adult patients with chronic insomnia. Their findings suggested that both exercise and CBT-I manifested better long-term effects in improving sleep, while pharmacological interventions were less effective in the long run.…”
Section: Comparison Of Exercise Therapy With Other Treatment Methodsmentioning
confidence: 99%
“…Furthermore, patients treated for pituitary macroadenomas or craniopharygniomas showed increased daytime somnolence despite normal sleeping patterns [26,27]. These patients may also benefit from aerobic exercise interventions, which have been shown in meta-analyses to positively impact disrupted sleep patterns in patients with chronic insomnia, as well as the elderly population as a whole [28,29]. No studies have been performed to date to analyze the impact of aerobic exercise on improvement of sleep quality after pituitary tumor surgery.…”
Section: Impaired Quality Of Life In Pituitary Tumor Patientsmentioning
confidence: 99%